Synergistic adsorption of Cu(II) and photocatalytic degradation of phenanthrene by a jaboticaba-like TiO2/titanate nanotube composite: An experimental and theoretical study - Kaiyu Cheng; Cai, Zhengqing; Fu, Jie; Xianbo Sun; Weiliang Sun; Long Chen; Dandan Zhang; Liu, Wen (Chemical Engineering Journal, 2019)
Combined water pollution with the coexistence of heavy metals and organic contaminants is of great concern for practical wastewater treatment. In this study, a jaboticaba-like nanocomposite, titanate nanotubes supported TiO2 (TiO2/TiNTs), was synthesized by a two-step hydrothermal treatment. TiO2/TiNTs had large surface area, abundant of –ONa/H groups and fine crystal anatase phase, thus exhibited both good adsorptive performance for Cu(II) and high photocatalytic activity for phenanthrene degradation. The maximum Cu(II) adsorption capacity on TiO2/TiNTs was 115.0 mg/g at pH 5 according to Langmuir isotherm model, and >95% of phenanthrene was degraded within 4 h under UV light. TiO2/TiNTs showed about 10 times higher observed rate constant (kobs) for phenanthrene degradation compared to the unmodified TiNTs. More importantly, the coexistence of Cu(II) promoted photocatalytic degradation of phenanthrene, because the incorporated Cu(II) in the lattice of TiNTs could trap photo-excited electron and thus inhibited the electron-hole recombination. Density functional theory (DFT) calculation indicated that the sites of phenanthrene with high Fukui index (f0) preferred to be attacked by OH radicals. The quantitative structure–activity relationship (QSAR) analysis revealed that the degradation intermediates had lower acute toxicity and mutagenicity than phenanthrene. TiO2/TiNTs also owned high stability, as only slight loss of Cu(II) and phenanthrene removal efficiency was observed even after four reuse cycles. The developed material in this study is of great application potential for water or wastewater treatment with multi-contaminants, and this work can help us to better understand the mechanisms on reaction between Ti-based nanomaterials and different kinds of contaminants.
Keywords: Adsorption; Combined pollution; Photocatalysis; Theoretical calculation; TiO; Titanate nanotube